Effect and mechanical mechanism of spontaneous breathing on oxygenation and lung injury in mild or moderate animal ARDS - Rui Yang; Leilei Zhou; Zongyu Chen; Shuang He; Siyu Lian; Yi Shen; Xianming Zhang (BMC Pulmonary Medicine, 2023)
Abstract Objective The present study aimed to determine the effect and mechanical mechanism of spontaneous breathing during mechanical ventilation on oxygenation and lung injury using Beagles dogs mild or moderate acute respiratory distress syndrome (ARDS) model. Methods After inducing mild or moderate ARDS by infusion of oleic acid, Eighteen Beagles dogs were randomly split into Spontaneous breathing group (BIPAPSB, n = 6), and Complete muscle paralysis group (BIPAPPC, n = 6),Six Beagles without ventilator support comprised the control group. Both groups were ventilated for 8 h under BIPAP mode. High-pressure was titrated TV to 6 ml/kg. A multi-pair esophageal balloon electrode catheter was used to measure respiratory mechanics and electromyogram. End-expiratory lung volume (EELV), gas exchange and respiratory variables were recorded in the process of mechanical ventilation. The contents of Interleukin (IL)-6 and IL-8 in lung tissue were measure using qRT-PCR. Besides, lung injury score was calculated in the end of mechanical ventilation. Results Based on the comparable setting of ventilator, BIPAPSB group exhibited higher safety peak transpulmonary pressure, abdominal pressure, EELV and P/F(PaO2/FiO2) than BIPAPPC group, whereas mean transpulmonary pressure, the mRNA levels of the IL-6 and IL-8 in the lung tissues and lung injury score in BIPAPSB group were lower than those in BIPAPPC group. Conclusion In mild to moderate ARDS animal models, during mechanical ventilation, SB may improve respiratory function and reduce ventilator-induced lung injury. The mechanism may be that spontaneous inspiration up-regulates peak transpulmonary pressure and EELV; Spontaneous expiration decreases mean transpulmonary pressure by up-regulating intra-abdominal pressure, thereby reducing stress and strain.